Intercultural Competence in Online Learning: Strategies for Inclusive and Equitable Education - Idris Maazin; Laith Nadir Zaki; Munir Fadlan Rafiq (Proceeding of the International Conference on Global Education and Learning, 2024)
In the era of digital transformation, online learning has become a dominant mode of education, emphasizing the need for intercultural competence to ensure inclusivity and equity. This study explores strategies for fostering intercultural competence in online learning environments by examining best practices in curriculum design, communication, and technological integration. Utilizing a qualitative research approach, data were collected through interviews with educators and students from diverse cultural backgrounds. The findings reveal that interactive learning activities, culturally responsive pedagogy, and adaptive learning technologies significantly enhance students’ intercultural competence. The study highlights the importance of fostering a supportive online community, encouraging cross-cultural collaboration, and implementing inclusive instructional strategies. These insights contribute to the development of equitable education policies that address cultural diversity in virtual classrooms.